2023
DOI: 10.3390/nu15132949
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 and Vascular Function in Healthy Women and Men: A Randomized Clinical Trial Comparing the Effects of Energy Restriction and Resveratrol

Abstract: Background: Sirtuin 1 (SIRT1) has been associated with longevity and protection against cardiometabolic diseases, but little is known about how it influences human vascular function. Therefore, this study evaluated the effects of SIRT1 activation by resveratrol and energy restriction on vascular reactivity in adults. Methods: A randomized trial allocated 48 healthy adults (24 women and 24 men), aged 55 to 65 years, to resveratrol supplementation or energy restriction for 30 days. Blood lipids, glucose, insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…We found no correlation between change in REE and FFM during LEA and suggest that downregulated tissue function (not loss of mass) may be responsible. In support of this, previous research has shown that lower REE in exercise-associated amenorrhea is not due to reduced tissue mass (Gonçalinho et al 2023). These findings identify that metabolic allostasis can occur rapidly during LEA and underscore the importance of using measures other than changes in body mass to indicate energy status.…”
Section: Physiological Function and Body Compositionsupporting
confidence: 71%
See 2 more Smart Citations
“…We found no correlation between change in REE and FFM during LEA and suggest that downregulated tissue function (not loss of mass) may be responsible. In support of this, previous research has shown that lower REE in exercise-associated amenorrhea is not due to reduced tissue mass (Gonçalinho et al 2023). These findings identify that metabolic allostasis can occur rapidly during LEA and underscore the importance of using measures other than changes in body mass to indicate energy status.…”
Section: Physiological Function and Body Compositionsupporting
confidence: 71%
“…For the first time, we demonstrate that in eumenorrheic non-exercising women assessed during the low-hormone phase of the menstrual cycle, resting FBF is decreased with just 3-days LEA. We also identify an association between resting FBF and REE, which may offer mechanistic insights into metabolic allostasis in response to LEA (Gavin et al 2009;Gonçalinho et al 2023).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…According to the RCT by Gonçalinho et al [62], endothelium-dependent FMD and endothelium-independent vasodilation (NMD) were assessed in a group of healthy subjects randomized to either receive a resveratrol supplement (500 mg/day) or a low-calorie diet (1000 kcal/day, providing over 50% energy restriction). An absence of difference was observed both for the FMD and the NMD (p = 0.443; p = 0.196, respectively), between the baseline and the post-treatment assessment, regarding the energy restriction group [62].…”
Section: Caloric Restrictionmentioning
confidence: 99%
“…These supplements could function as SIRT activators, enhancing the pharmacological perspective of SIRT use. Researchers have sought to investigate the role of SIRT1 in vascular function, in cardioprotection and in the metabolic properties of skeletal muscle relating to mitochondrial function and muscle fibre properties (Gonçalinho et al., 2023). Despite these efforts, further investigations are needed to better elucidate the mechanisms and therapeutic possibilities of SIRT1.…”
mentioning
confidence: 99%